Polysialylated Neural Cell Adhesion Molecule Serum Levels in Normal Children - Glüer, Sylvia; Wunder, Michael A; Schelp, Carsten; Radtke, Elgin; Gerardy-Schahn, Rita (Pediatric research, 1998)
Serum concentrations of polysialylated neural cell adhesion molecule (PSA-NCAM), a developmentally regulated form of the NCAM, have been recently described to be elevated in children with rhabdomyosarcoma and neuroblastoma, proving PSA-NCAM to be a tumor marker of diagnostic relevance to these malignancies. The present investigation was undertaken to define age-dependent reference intervals in normal children. Serum concentrations of polysialylated NCAM were determined in 366 children aged newborn to 17 y and in 18 adult patients by an immunoluminescence assay using the polysialic acid-specific MAb 735. Serum levels in newborn children were 51.7 kU/L (mean +/- 12.0 kU/L SD), whereas in adult patients they were 9.9 kU/L (mean +/- 3.5 kU/l SD). Assigning the patients to 14 different age groups, a gradual decay of PSA-NCAM serum concentrations was observed, and therefore, mean levels and empirical interpolated percentiles were determined for every age group. Applying specially fitted logistic functions, two different sigmoid graphs were obtained describing the age-dependent decrease of serum PSA-NCAM during the neonatal period and during childhood. The age at which the levels reach half the initial value was located at 3.1 d (mean +/- 2 d SE) and 14 y (mean +/- 1 y SE), respectively. There was no difference between male and female individuals. Repeated measurements revealed variations below 10%. For the first time, our study describes serum levels of PSA-NCAM in children of different age and their gradual decay until adulthood.